OPTIMALISASI WAKAF PRODUKTIF - Asytuti, Rinda (At-Taradhi, 2012)
Wakaf management is shifting. In the past, wakaf funds and inventory were used mainlyto support tombs and schools. Recently, they are managed for productive ends without reducingthe wakaf assets themselves. This is possible to take place after Law No. 41 (2004) was passed andthe establishment of the Body for Indonesian Wakaf Management (Badan Wakaf Indonesia -BWI) by the Government. Since then, wakaf is not only limited to non-moving assets, such asland, but it also includes cash wakaf . According to the records of Dompet Dhuafa, a non govern-mental institution that manages Islamic philanthropic funds (alms, tithes, donations and wakaf ),there is a substatial increase in the amount of wakaf money coming in. It is crucial then toimprove wakaf management to a more professional one, so that wakaf funds can benefit theMuslim community in Indonesia and increase their welfare.